Symposium 4: Challenges for Chinese Learners in Sino-UK Intercultural Online Interactions--Case Study of an eChina~UK Project Course - Zhang, Zhenhong; Huang, Ronghuai (Proceedings of the International Conference on Networked Learning, 2008)
Education has gone beyond national boundaries with the help of Internet and other network technologies. People from various countries and places have more opportunities to learn together online through computer mediated communications and collaboration. However, technological possibilities do not mean everything. Cultural diversity has imposed new challenges on intercultural networked learning and makes it much more complex than uni-cultural education. Identification of cultural challenges and understanding of their causes become an important part of pedagogy in the era of cross-cultural networked learning. This paper studies the case of an online course "Intercultural E-learning Communities" designed and developed collaboratively by partners from Britain and China. It is found that in intercultural online interactions of the course, Chinese learners participated much less, wrote much less, and put forward much less discussion topics than their British counterparts. In-depth interviews were conducted with some of the Chinese learners, analysis of which reveals that information technology and the language of English used in the course are not major challenges to Chinese learners in online interactions. Rather, difficulty in 'speaking' in English, difficulty in understanding British participants' messages, difficulty in putting forward viewpoints, and difficulty in obtaining teacher's direction are the major challenges for Chinese online learners. In view of the impact of Chinese culture, face problem in particular, and traditional education on online learning, it is concluded that the need to preserve face, ask-for-answer tendency in learning, and lack of skills in analytical thinking are the three major causes for these challenges. Conclusions of the analysis shed light on the cultural impact on intercultural online interactions, and offer insights into the design, development, and tutoring of intercultural online courses.